An overlooked earlier name for the bird blow fly genus Protocalliphora Hough (Diptera: Calliphoridae) - Evenhuis, Neal L. (Zootaxa, 2012)
Protocalliphora, a genus-group name of calliphorid flies proposed by Hough (1899) is a well-known blood-feeding obligate parasite of a number of species of birds throughout the Nearctic and Palaearctic Regions where the larvae attack young birds in their nests sometimes causing death. An excellent comprehensive work on the taxonomy and biologies of the species of the genus was published by Sabrosky et al. (1989). Their work treated 26 species in the genus and gave records of more than 140 species of birds recorded as hosts.